2018
DOI: 10.1140/epjc/s10052-018-6372-1
|View full text |Cite
|
Sign up to set email alerts
|

Higher bottomonium zoo

Abstract: In this work, we study higher bottomonia up to the nL = 8S , 6P, 5D, 4F, 3G multiplets using the modified Godfrey-Isgur (GI) model, which takes account of color screening effects. The calculated mass spectra of bottomonium states are in reasonable agreement with the present experimental data. Based on spectroscopy, partial widths of all allowed radiative transitions, annihilation decays, hadronic transitions, and open-bottom strong decays of each state are also evaluated by applying our numerical wave function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
79
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 103 publications
14
79
3
Order By: Relevance
“…For theΥ(3D) state, the dielectron width was obtained to be 0.095 +0.028 −0.025 keV, which indicated that the predominantly 3 3 D 1 bb state can be produced in the e + e − annihilation process with the high statistics data. Furthermore, the decay width of the 3 3 D 1 bb state was obtained as 54.1 MeV [35] which is comparable with the measurement by the Belle Collaboration [25] (see Eq. (1)).…”
Section: Nd Statessupporting
confidence: 86%
See 2 more Smart Citations
“…For theΥ(3D) state, the dielectron width was obtained to be 0.095 +0.028 −0.025 keV, which indicated that the predominantly 3 3 D 1 bb state can be produced in the e + e − annihilation process with the high statistics data. Furthermore, the decay width of the 3 3 D 1 bb state was obtained as 54.1 MeV [35] which is comparable with the measurement by the Belle Collaboration [25] (see Eq. (1)).…”
Section: Nd Statessupporting
confidence: 86%
“…The 1G bb masses are predicted around 10590 MeV which are slightly above the BB threshold at 10.56 GeV. Our predicted masses of 1G bb states seem to be larger than the results given by the quark potential models [5,[34][35][36], but very close to the results from the lattice QCD [50], where the masses of 4 −+…”
Section: High Orbital Excited Statessupporting
confidence: 72%
See 1 more Smart Citation
“…The general consensus is that Υ(10860) and Υ(11020) correspond to the S -wave vector bb states Υ(5S ) and Υ(6S ), respectively [3][4][5][6][7][8][9][10][11][12]. However, if one assigns Υ(10860) to Υ(5S ), we should face several problems, such as (i) the mass of Υ(5S ) from the recent potential model calculations is about 70 − 90 MeV lower than the observed value of Υ(10860) [8][9][10][11][12]; (ii) the mass splittings m[Υ(5S ) − Υ(4S )] th ≃ 210 MeV and m[Υ(6S ) − Υ(5S )] th ≃ 180 MeV predicted within various potential models [8][9][10][11][12] For the newly observed Y(10750), we also meet several problems if we explain it with a pure S -, or D-wave vector bottomonium state. According to the predictions in potential models, the Y(10750) resonance lies between the vector states Υ(5S ) and Υ 1 (3D) [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Our predicted mass of 4505 MeV is close to it. Recently, Zhi-Gang Wang has tentatively assigned X(4500) as the first radial excited state of the axial-vector-diquark-axial-vector-antidiquark cscs tetraquark state [43]. However, the predicted mass of this state not enough to interpret this state as an exotic state, we need to look for its decay properties also.…”
Section: Resultsmentioning
confidence: 99%